Imaging and MR Spectroscopy in Papillary Craniopharyngioma - Mahajan, Ashima; Bheru Dan Charan,; Sushant Agarwal,; Vinay Goel,; Devarajan Sebastian, Leve Joseph; Suri, Vaishali; Suri, Ashish; Garg, Ajay (Acta medica Lituanica, 2024)
Sellar-suprasellar masses exhibit a diverse range of differential diagnoses and it is feasible to establish a preliminary diagnosis before surgery by evaluating conventional CT scans and contrast-enhanced MRI results. Nevertheless, certain cases may present with inconclusive findings, making it challenging to anticipate the underlying tissue composition accurately through imaging alone. Researchers have explored the application of Proton MR spectroscopy in analyzing suprasellar tumors, and their investigations have revealed that it can complement traditional MRI by enhancing the accuracy of preoperative diagnoses. In this context, we report three biopsy-proven cases of suprasellar papillary craniopharyngioma where the MRS spectra derived from the solid component exhibited noticeable lipid peaks alongside reduced levels of choline and NAA. These findings played a pivotal role in facilitating the correct preoperative identification of papillary craniopharyngioma.
Keywords: Craniopharyngioma; Spectroscopy; Suprasellar